Et Tu Brute? the Roles of Subordinate–Supervisor Similarities on the Relationship Between Abusive Supervision and Employee Silence Behavior: A Study from the Subordinates’ Perspectives - Lopez-Bohle, S (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The current study examined the moderating effects of subordinate–supervisor similarities on abusive supervision and employee silence relationships. We addressed the question of whether employees’ silence reactions are alleviated or aggravated when the abuse comes from a supervisor who shares a similar gender and other sociodemographic attributes with the employee. The results indicated that abusive supervision led to more silence behavior and supported the moderating effect of perceived sociodemographic similarity on this relationship. However, regardless of gender similarities with their supervisors, the findings postulated that employees experiencing abusive supervision were more likely to remain silent at work. When there is a perceived sociodemographic similarity between the employee and the supervisor, abusive supervision has been found to have a harsher influence on employee’s silence behavior. These findings help us better understand the antecedents of employee silence behavior and provide important implications for subordinate–supervisor similarity dynamics in exposure to abusive supervision. © 2024 by the authors.